2021
DOI: 10.1183/13993003.04125-2020
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung disease increases susceptibility to and severity of COVID-19

Abstract: BackgroundThere are limited data regarding the relationship between interstitial lung disease (ILD) and the natural course of coronavirus disease 2019 (COVID-19). In this study, we investigate whether patients with ILD are more susceptible to COVID-19 than those without ILD and evaluate the impact of ILD on disease severity in patients with COVID-19.MethodsA nationwide cohort of patients with COVID-19 (n=8070) and a 1:15 age-, sex-, and residence-matched cohort (n=121 050) were constructed between January 1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 37 publications
3
63
1
5
Order By: Relevance
“…We identified here that ACE2, TMPRSS2, and Furin are highly expressed on small airway epithelium and alveolar region in both IPF and LAM patients, especially high in IPF, which indicates that LAM and IPF patients could be more vulnerable to COVID-19 infections, and this could further exaggerate due to smoking history and comorbidities. Our findings provide the first histopathological evidence supporting the recent observational study from Lee et al [29] The study reported that patients with ILD had higher susceptibility to COVID-19 and had more severe clinical outcomes from COVID-19, especially patients with IPF [29]. However, the reason for this increased risk for COVID-19 in IPF patients was not provided at a tissue level.…”
Section: Discussionsupporting
confidence: 83%
“…We identified here that ACE2, TMPRSS2, and Furin are highly expressed on small airway epithelium and alveolar region in both IPF and LAM patients, especially high in IPF, which indicates that LAM and IPF patients could be more vulnerable to COVID-19 infections, and this could further exaggerate due to smoking history and comorbidities. Our findings provide the first histopathological evidence supporting the recent observational study from Lee et al [29] The study reported that patients with ILD had higher susceptibility to COVID-19 and had more severe clinical outcomes from COVID-19, especially patients with IPF [29]. However, the reason for this increased risk for COVID-19 in IPF patients was not provided at a tissue level.…”
Section: Discussionsupporting
confidence: 83%
“…Disease subtype appears to be important in disease susceptibility. In the study by LEE et al [11], patients with all subtypes of ILD examined demonstrated increased frequency of infection, with the exception of chronic hypersensitivity pneumonitis, and the effect was most pronounced in patients with IPF. In the study by ESPOSITO et al [12], usual interstitial pneumonitis pattern (typically seen in IPF) was more common in non-survivors, but this did not reach statistical significance.…”
Section: Covid-19 Infection In Patients With Existing Ildmentioning
confidence: 92%
“…It appears that patients with ILD are indeed more susceptible to contracting COVID-19. In a Korean study of patients with COVID-19 compared with age, sex and location matched controls, LEE et al [11] found that 0.8% of COVID-19 patients had an ILD diagnosis versus 0.4% of matched controls giving an adjusted OR for ILD of 2.02 (95% CI 1.54-2.61; p<0.001). LEE et al [11] also demonstrated that patients with ILD in the COVID-19 cohort were more likely to have severe disease compared with those without (49.3% versus 13.1%, adjusted OR 2.32, 95% CI 1.24-4.01) and patients with ILD are also more likely to succumb to infection.…”
Section: Covid-19 Infection In Patients With Existing Ildmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the proportion of patients with previous ILD was significantly higher in the COVID-19 cohort than in the control cohort (0.8% versus 0.4%; P < .001), indicating that they were more susceptible to becoming infected (oddas ratio [OR] = 2.02; 95% confidence interval [95% CI ], 1.54-2.61). 8 However, we do not currently know how this risk will change after vaccination in this group of patients.…”
Section: Are Patients With Pulmonary Fibrosis More Susceptible To The...mentioning
confidence: 97%